One simple idea : turn your dreams into a licensing goldmine while letting others do the work - Key, Stephen (New York : McGraw-Hill, 2011)
Provides insight into the process of licensing and introducing products, with step-by-step instructions for inventors who are interested in earning an income from their ideas
1. The power of one simple idea -- 2. Find your million-dollar idea -- 3. Prove your idea -- 4. Protect your idea -- 5. Prepare to pitch your idea -- 6. Submit your idea to potential licensees -- 7. Bring your ideas to market
Includes index
Keywords: Entrepreneurship; Inventions; Inventions -- Marketing; New business enterprises -- Management